THE UTILIZATION OF MEDICINE PLANTS IN AMBAN RESIDENTS IN INCREASING KNOWLEDGE TOWARDS HERBAL TREATMENT - Maturahmah, Enik; Revisika; Rahmi, Elvi; Sandy, Gilang Ary (Lux Mensana: Journal of Scientific Health, 2022)
Medicinal plants are all species of medicinal plants that are known and believed to have efficacy as traditional medicine, then they can be used as self-medication. Amban Village is one of the villages located in Kab. Manokwari, West Papua. The majority of the villagers have large yards and gardens because the villagers are generally farmers. The yard as a living environment provides a variety of natural resources that have not been used optimally, one of which is the use of surrounding plants. There are unidentified plants which has role as traditional medicine. This causes the population become very dependent on chemical drugs even for treat minor ailments. In addition, these plants are considered weeds and must be destroyed, either by spraying herbicides or by clearing them. This will certainly disrupt the ecosystem and plant diversity in this environment. The condition of ignorance of Amban village community is the reason for this community activity. The purpose of this activity is to optimize the role of plants that around as an effort to self-medicate and to support the "back to nature" community interest. The method used in this activity is to use socialization for the participants consisting of several villagers. The results of the service showed that there was an increase in villagers’ knowledge who were present at the service activity about the use of surrounding plants as herbal medicine. This can be seen from the ability of the participants to answer questions from the activist.